The internal region of CtIP negatively regulates DNA end resection. Issue 10 (29th April 2020) - Howard, Sean Michael; Ceppi, Ilaria; Anand, Roopesh; Geiger, Roger; Cejka, Petr
Abstract: DNA double-strand breaks are repaired by end-joining or homologous recombination. A key-committing step of recombination is DNA end resection. In resection, phosphorylated CtIP first promotes the endonuclease of MRE11–RAD50–NBS1 (MRN). Subsequently, CtIP also stimulates the WRN/BLM–DNA2 pathway, coordinating thus both short and long-range resection. The structure of CtIP differs from its orthologues in yeast, as it contains a large internal unstructured region. Here, we conducted a domain analysis of CtIP to define the function of the internal region in DNA end resection. We found that residues 350–600 were entirely dispensable for resection in vitro . A mutant lacking these residues was unexpectedly more efficient than full-length CtIP in DNA end resection and homologous recombination in vivo, and consequently conferred resistance to lesions induced by the topoisomerase poison camptothecin, which require high MRN–CtIP-dependent resection activity for repair. This suggested that the internal CtIP region, further mapped to residues 550–600, may mediate a negative regulatory function to prevent over resection in vivo . The CtIP internal deletion mutant exhibited sensitivity to other DNA-damaging drugs, showing that upregulated resection may be instead toxic under different conditions. These experiments together identify a region within the central CtIP domain that negatively regulates DNA end resection.